Pb-214/Bi-214-TCMC-Trastuzumab inhibited growth of ovarian cancer in preclinical mouse models - Metebi, Abdullah; Kauffman, Nathan; Xu, Lu; Singh, Satyendra Kumar; Nayback, Chelsea; Fan, Jinda; Johnson, Nathan; Diemer, John; Grimm, Terry; Zamiara, Mike; Zinn, Kurt R. (Frontiers in Chemistry, 2024)
Better treatments for ovarian cancer are needed to eliminate residual peritoneal disease after initial debulking surgery. The present study evaluated Trastuzumab to deliver Pb-214/Bi-214 for targeted alpha therapy (TAT) for HER2-positive ovarian cancer in a mouse model of residual disease. This study is the first report of TAT using a novel Radon-222 generator to produce short-lived Lead-214 (Pb-214, t1/2=26.8 min) in equilibrium with its daughter Bismuth-214 (Bi-214, t1/2=19.7 min); referred to as Pb-214/Bi-214. The decay of Pb-214/Bi-214 yielded a-particles for TAT. In this study, Trastuzumab was conjugated with TCMC chelator and radiolabeled with Pb-214/Bi-214 for targeting HER2+ ovarian cancer in mouse models. Two human ovarian cancer cell lines were tested for HER levels and then compared. SKOV3 cells had 590,000+5,500 HER2 receptors/cell compared with OVCAR3 cells at 7,900±770. In vitro clonogenic assays with SKOV3 cells showed significantly reduced colony formation after Pb-214/Bi-214-TCMC-Trastuzumab treatment compared with controls. Nude mice bearing luciferase-positive SKOV3 or OVCAR3 tumors were treated with Pb-214/Bi-214-TCMC-Trastuzumab or appropriate controls. Two 0.74 MBq doses of Pb-214/Bi-214-TCMC-Trastuzumab significantly suppressed the growth of SKOV3 tumors for 60 d, without toxicity, compared with three control groups (untreated, Pb-214/Bi-214-TCMC-IgG1, or Trastuzumab only). Mice-bearing OVCAR3 tumors had effective therapy without toxicity with two 0.74 MBq doses of Pb-214/Bi-214-TCMC-trastuzumab or Pb-214/Bi-214-TCMC-IgG1. Together, these data indicated that Pb-214/Bi-214 from a Rn-222 generator system was successfully applied for TAT. Pb-214/Bi-214-TCMC-Trastuzumab was effective to treat mouse xenograft models. Advantages of Pb-214/Bi-214from the novel generator systems include high purity, short half-life for fractioned therapy, and hourly availability from the Rn-222 generator system. This platform technology can be applied for a variety of cancer treatment strategies.